Understanding the glucose tolerance of an archaeon β-glucosidase from Thermococcus sp. (1st December 2019) - Sinha, Sushant K.; Prakash Reddy, K.; Datta, Supratim
Abstract: β-glucosidase hydrolyzes the β-1, 4 linkage of cellobiose, a product generated from the action of endoglucanase and cellobiohydrolase on cellulose, and generates glucose. Accumulated glucose during saccharification leads to product inhibition of β-glucosidase, which in turn cause an accumulation of cellobiose and inhibition of other cellulolytic enzymes. Thus, glucose tolerant and active β-glucosidase is required for the efficient saccharification of biomass. O08324 is a glucose tolerant β-glucosidase isolated from archaeon Thermococcus sp. which shows no loss in enzyme specific activity in the presence of up to 4 M glucose and is active at 78 °C. Since O08324 has such high glucose tolerance, knowing the rationale for glucose tolerance will be helpful in engineering glucose tolerant β-glucosidase. In the present study, we designed mutations at eleven sites across the gatekeeper, aglycone, and glycone region. Based on the kinetic studies of O08324 mutants, the gatekeeper residues at positions 160, 166, 167, 168, and the aglycone binding residue 156 were identified to play a role in glucose inhibition. However, only residues at the tunnel entrance, and not all gatekeeper residues contribute to glucose tolerance. This study sheds some light on the unusual glucose tolerance of O08321 archaeal GH1 β-glucosidase. Graphical abstract: Image 1 Highlights: Accumulated glucose during saccharification causes β-glucosidase product inhibition. O08324 from Thermococcus sp. shows no loss in specific activity up to 4 M glucose. Hydrophobicity and steric interactions at tunnel entrance regulate glucose tolerance. All gatekeeper residues at tunnel entrance do not contribute to glucose tolerance.